Treatment of Acute Lung Abscesses Considering their Non-Respiratory Function in Patients with Diabetes - Okhunov A.O1., Israilov R.I.1, Khamdamov Sh.A.1, Azizova P.X.1, Anvarov K.D.1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
During the examination and treatment of 465 patients with acute lung abscesses on the background ofdiabetes mellitus, a preoperative preparation program was developed that takes into account the phase of theprocess (group 1 - septic course of the process, group 2 - stabilization, group 3 - remission), the severity ofendotoxemia and non-respiratory lung function. Patients of the 1st group against the background of basiclong-term intra-arterial catheter therapy used the scheme of correction of non-respiratory function of thelungs that we developed, sanitized purulent foci with an electrolyzed solution of sodium hypochlorite. In202 (79.9%) of 254 patients of the 1st group, it was effective that allowed to refuse the operation, while only52 (40.6%) were not operated on in the 2nd, and 26 in the 3rd (31.3%) patients. In parallel, a pronouncednormalizing effect was achieved in correcting the degree of violation of non-respiratory lung functionagainst the background of delimitation and stabilization of the process. This allowed in 109 (60.9%) of 179operated patients to confine themselves to lung resection with 8.7% of postoperative complications in the 1stgroup versus 18.4% in the 2nd and 24.6% in the 3rd, which emphasizes the effectiveness of our preoperativepreparation.